Migrants Remittances Influence on Fiscal Sustainability in Dependent Economies - Liliana Simionescu; Dalina Dumitrescu (Amfiteatru Economic Journal, 2017)
Migrants' remittances are an important financial flow to their country of origin. Remittances sent by migrants reduce the level and severity of poverty in developing countries. Householders use this money received from migrants for their private consumption and their investments. This paper aims to analyse the impact of remittances on economic growth, private consumption, private investments and the government tax revenue in low and upper middle-income countries. The paper highlights one of the important migration's drivers, respectively economic reasons. Our findings are based on data from 74 developing countries collected for the period between 1989 and 2015. Using a panel data set , our results show that migrants' remittances are positively related with economic growth and private consumption expenditure. Moreover, the results also indicate that variables such as age dependency ratio and the number of individuals holding an account at a financial institution are statistically significant in models having GDP per capita and private consumption as dependent variables. Furthermore, our results show that migrants' remittances are associated with government tax revenue and real interest rate when instrumental variables were used.
Keywords: F24; F21; H7; E62; E52; 330; migrants' remittances; consumption; investment; government tax revenue; fiscal policy; monetary policy